Bioavailability and molecular recognition between secondary metabolites of Euphorbia hirta L. and 5-lipoxygenase using fragment molecular orbital method and pair interaction energy decomposition analysis - Marcano, Emildo; Sánchez, Ysbelia (Revista de la Facultad de Farmacia, 2024)
Is presented the bioavailability analysis for seven secondary metabolites from Euphorbia hirta L. (Euphorbiaceae). The bioactivity score, the molecular similarity analysis for each secondary metabolite, and the molecular docking 5-LOX/metabolite complex are also presented. For the similarity analysis, it is referenced the structure of allosteric LOX-5 inhibitor 3-acetyl-11-keto-beta-boswellic acid (AKBA). The fragment molecular orbital method (FMO) and pair interaction energy decomposition analysis (PIEDA) were applied to evaluate the interaction energy between secondary metabolites and the 5-LOX active site. Log P values of all the secondary metabolites studied were found to be higher than 5, contrary to what was expected with Lipinski’s rules of five. The reference LOX-5 ligand has a high electrostatic potential similarity with most secondary metabolites studied, with values from 0.667 to 0.730. Both AKBA and metabolites ligands were wedged between the two domains of LOX-5, and the main residues contact were LEU-66, ARG-68, VAL-110, HIS-130, ILE-126, GLN, 129, and LYS-133. The PIEDA analysis showed that stabilization in the 5-LOX active site is mainly dominated by hydrophobic interactions, with values up to -35 Kcal/mol. Due to the low presence of terminal-OH groups, electrostatic origin, and charge transfer interaction energies are also important but have values of less than 20 Kcal/mol.